Dinâmicas sociais e desenvolvimento territorial no território Serra do Brigadeiro: atores, redes e instituições - Alair Ferreira de Freitas (2015)
This research analyzed on social relations subjacent to organizational arrangement that operationalizes the Rural Territorial Development Policy (Pronat) of Agrarian Development Department (MDA), explaining the way the actors establish their coalitions, create rules and reframe the territory. Our goal is to understand, by qualitative methodology, how the creation of Serra do Brigadeiro Territory (TSB), in the scope of this policy, influenced the interaction among the actors who act on it and how the configuration of this actors network conditioned the implementation of public policies and, in this way, the rural territorial development. Looking for a relational approach, it was mobilized two different axes from a theoretical explicative model, the neoinstitucionalism and the new economic sociology, approaching categories that involve the analysis of social relations and others that contextualize them institutionally, elaborating an analytic chart oriented to the comprehension of the social dynamic in rural territories. It was found in this research that the TSB is a contingent quota, permeated by conflicts, indicating that there are deep social logics that conduct the experience to a direction and not to another, whose explanation is historical. The network sociogenesis which operationalizes the Pronat at TSB refers to Basic Ecclesial Communities, to union movement of rural workers and to the creation of Serra do Brigadeiro State Park, historical experiences that modeled the organizations trajectory from this region and reconfigured the social relations. The policy network segmentation and the conflicts that compose it defined the processes of TSB institutionalization, directing the content of collective agreements and of the informal and formal standards that oriented the policy and the social interactions at Territorial Board. The social representations of actors about the territory and about the way the network was structured, their participation in other networks out of territory and the allocation of social capital of municipalities were central elements that guided historically the actors engagement on TSB network and, then, led their ways of intervention on the territory. Another conditioning element of the actors intervention are the standards and the collective agreements, creating institutional arrangements erected from the agreed interests by those who had assumed more central positions at TSB network and looking for generating stability and sense to their practices and achieve their interests. This study also found that actors, networks and institutions synthesize the main elements of the social dynamic of the territory, which is largely conditioned by the politics more than by the policy. Therefore, the territorialization of the space and of public policy at TSB depends on the organizational arrangements and on the prevailing institutions, on the way the actors interact among them and reproduce the power relations. It concludes that the TSB has propitiated the expansion of engagement scales to the organized social actors, especially those from civil society, in other networks and with actors from public sector, which without a policy hardly would relate to each other. On the other hand, it perceives the reproduction of marginalization of those who does not have the same organizational level.